Study on influence of braking performance on automatic stopping accuracy of standard metro train - AN Zhen; LI Long; LI Pengfei; LI Runhua (机车电传动)
The problem of exceeding or short of standard line under ATO mode of metro train has always troubled many urban rail transit users, in order to improve the parking accuracy of series standard metro trains under ATO mode, the electric braking force, electric air coordination, air braking preload control, air braking force, brake shoe, brake pad and wheel rail adhesion that affect the vehicle braking performance were analyzed. Combined with the actual operation measurement data of existing trains, it was verified that the exertion accuracy of electric braking force, electric air coordination parameters, air preload, brake shoe, brake pad friction coefficient and surface state, as well as wheel rail surface state will affect the train parking accuracy to varying degrees. Through test debugging and line verification, the braking performance optimization suggestions to improve the automatic parking accuracy of serial standard metro trains were given.